2017
DOI: 10.1002/we.2152
|View full text |Cite
|
Sign up to set email alerts
|

Large‐eddy simulations of wind‐farm wake characteristics associated with a low‐level jet

Abstract: In this study, we performed a suite of flow simulations for a 12-wind-turbine array with varying inflow conditions and lateral spacings, and compared the impacts of the flow on velocity deficit and wake recovery. We imposed both laminar inflow and turbulent inflows, which contain turbulence for the Ekman layer and a low-level jet (LLJ) in the stable boundary layer. To solve the flow through the wind turbines and their wakes, we used a large-eddy simulation technique with an actuator-line method. We compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…A similar phenomenon has been observed in the mesoscale weather model simulations of an infinite wind farm [48]. Recently, Na et al [49] performed LES of a small wind farm with 12 turbines arranged in three columns and four rows with an LLJ above it in a spanwise periodic domain. They report faster wake recovery due to the enhanced vertical kinetic energy flux created by the LLJ.…”
Section: Introductionsupporting
confidence: 72%
“…A similar phenomenon has been observed in the mesoscale weather model simulations of an infinite wind farm [48]. Recently, Na et al [49] performed LES of a small wind farm with 12 turbines arranged in three columns and four rows with an LLJ above it in a spanwise periodic domain. They report faster wake recovery due to the enhanced vertical kinetic energy flux created by the LLJ.…”
Section: Introductionsupporting
confidence: 72%
“…For ALM, although the relationship between velocity and force is correct, a tip loss correction is suggested by Shen [19] due to the inconsistency between 2D airfoil data and attack angle of the 3D blade. This tip loss correction is employed in this study to compensate for the tip loss effect of wind turbine blade as shown in Equations (7) and (8)…”
Section: Tip Loss Correctionmentioning
confidence: 99%
“…Combining with the LES model, ALM can make good simulations of velocity field and turbulence field in the wake region [2,3] and it has advantages in wind turbine simulations when the inlet condition is complex, such as the atmospheric boundary layer condition [4,5]. Secondly, due to 2 of 19 its low computational cost, ALM can be used in large-scale problems [4,[6][7][8] and can be easily coupled with structural models [9,10]. Therefore, ALM is suitable for wind farm simulations and fluid-structure interaction simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the increasing physical dimensions of wind turbine heights over time, and particularly offshore, mean LLJs may more frequently intersect with the wind turbine rotor plane [24,25]. When a LLJ occurs within the rotor plane, changes to the distributions of turbulent kinetic energy, shear, wind speed and wind direction [26,27] may increase energy production and enhance wind turbine wake recovery [28,29]. However, it is also likely to be associated with enhanced static and mechanical loading, fatigue cycles and deflections [30].…”
Section: Introductionmentioning
confidence: 99%